Nursing of a patient with shoulder-hand syndrome after stroke treated with warm moxibustion scrapping therapy (温灸刮痧技术治疗中风后肩手综合征1例的护理体会) - HONG Shuang (洪双) (中西医结合护理)
This paper summarized the nursing measures for a patient with shoulder-hand syndrome after stroke treated with warm moxibustion scrapping therapy. Based on the nursing assessment and Traditional Chinese Medicine syndrome differentiation, warm moxibustion scrapping therapy was carried out to relief the pain of suffered limbs and improve the motor function and patient’s self-care ability of daily living. (本文总结1例运用温灸刮痧技术治疗肩手综合征的护理经验。患者入院后即开展护理评估, 明确护理重点, 辨证分型, 运用温灸刮痧技术, 缓解患肢疼痛, 改善肢体运动功能, 提升患者生活自理能力。)